KEBIJAKAN WAJAR DIKDAS 9 TAHUN POLA PONDOK PESANTREN SALAFIYAH - Murtadho, Ali (Forum Tarbiyah, 2012)
One thing that is not separated in the discourse of education in Indonesia is a pondok resantren (Islamic boarding school). This is the model of the first and the oldest education system in  Indonesia. Its presence has been inspiring to the models and systems of the present found. Even it is not weathered over the age with all the changes. Therefore many experts, both locally and internationally consider it as their study materials. One of the boarding schools studied is salafiyah. Ponpes Salafiyahin its history has been doing a lot of incredible breakthroughs. One such is that ponpes salafiyahhas implemented 9 years of compulsory education (Wajib Belajar Pendidikan Dasar) in the pattern of boarding school. The implementation of this policy is one form of awareness of the boarding school in educating the nation's children. Therefore, the role of Ponpes Salafiyahin Indonesian education is not able to be underestimated since it is also recognized in the national education system.